LETHAL OUTCOMES IN INFLUENZA: CLINIC-PATHOLOGICAL APPROACH TO IMMEDIATE DEATH CAUSES - A. A. Yakovlev; V. A. Zinserling; E. V. Esaulenko (Журнал инфектологии)
Influenza is one of the most outspread infections not seldom leading to lethal outcomes. Immediate death causes are analyzed rarely. Material and methods. We provided clinic-pathological correlations in 23 cases with lethal outcomes in 1999, 15 – in 2009, 31 in 2016 and 10 in 2017. Results. It was shown that in 2009 and 2017 most frequent lethal outcomes were related to bacterial superinfection in elderly people with severe background pathology. In 2009 and 2016 the leading role played respiratory distress syndrome predominantly in people of middle age, frequently with obesity. Conclusions: by circulation of different strains of influenza A virus the disease has substantial peculiarities. Lethal outcomes may be related: 1) severe respiratory insufficiency due to respiratory distress syndrome; 2) generalized viral infection; 3) secondary bacterial pneumonia; 4) aggravation of severe somatic diseases. Many aspects of pathogenesis need complex.study.